REVIEW ON AZADIRACHTA INDICA (ANTIBACTERIAL ACTIVITY) AS A MEDICINAL PLANT. - 1. Jyoti Yadav, 2. Neetu Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Neem has become valuable plant in the world which shows the solutions for hundreds to thousands of problems. Leaves of neem plant have been used in treating eczema and dermatophytic infections. It has well documented antihyperglycemic, anti-inflammatory and antimicrobial properties. Neem has incredible healing qualities in terms of human health. It has been proven to have anti- ageing, antibacterial, antifungal, antiseptic, antiviral, anti-inflammatory, antipyretic, antiulcer qualities and also contain analgesic compounds. Neem is a fast- growing evergreen popular tree found commonly in India, Bangladesh, Myanmar, Pakistan, Africa and America. The current review describes the major biological activities, antibacterial properties of some of the neem compounds isolated.